Association of menopause and type 2 diabetes mellitus. Issue 3 (March 2019) - Ren, Yongcheng; Zhang, Ming; Liu, Yu; Sun, Xizhuo; Wang, Bingyuan; Zhao, Yang; Liu, Dechen; Liu, Xuejiao; Zhang, Dongdong; Liu, Feiyan; Cheng, Cheng; Liu, Leilei; et al.
Abstract: Objective: Limited information is available on the direct effect of menopause and risk of type 2 diabetes mellitus (T2DM) among women with different metabolic types. We aimed to investigate whether menopause is a direct risk factor for T2DM. Methods: In this population-based cross-sectional study, women were recruited from a rural area of China from July to August 2013 and July to August 2014. Multivariate logistic regression analysis yielded adjusted odds ratios (ORs) and 95% CIs. Mediation analysis was performed to examine the contribution of age to menopause status-related T2DM. Results: We included 8, 191 women (median age 56, interquartile range 47-65). The prevalence of T2DM was 13.22%. Risk of T2DM was increased with postmenopause versus premenopause status after adjustment (adjusted OR [aOR] = 1.90, 95% CI = 1.51-2.37), with the strongest association between postmenopause status and T2DM among women with body mass index (BMI) <24.0 kg/m 2 (aOR, 3.25; 95% CI, 1.98-5.32). Risk of T2DM was increased with postmenopause status interacting with BMI, hypertension, triglycerides level, and waist circumference. On mediation analysis, age partially mediated the menopause status–T2DM association (indirect effect: OR = 1.27, 95% CI = 1.13-1.46; direct effect: OR = 1.88, 95% CI = 1.49-2.36). Conclusions: The prevalence of T2DM is high among women, and postmenopause status might be a stable and significant risk factor for T2DM; especially, postmenopausal women with normal weight should not be ignored in addressing the risk.